Chain of nacional cocoa marketing in Los Rios province in Ecuador - Morales Intriago, Fátima (2018)
The production of cocoa in Ecuador is a very important thing. It generates significant sources of economic income and provides jobs for thousands of people. Small farmers who trade with intermediaries produce the National type cocoa known also as “Arriba”. This is a common practice in the country and the province of Los Ríos is not out of this situation. The general objective of the work was to analyze the commercialization of National type cacao in the province of Los Ríos, Ecuador. Specifically, we sought to identify, analyze and discuss the main marketing channels managed by small producers. The work expresses the need for intervention by the State so that the producer can commercialize the product directly. In addition, it can contribute to the empowerment of producers with respect to the commercialization of cocoa. Qualitative and quantitative data were collected. Interviews were conducted with small producers in the fieldwork. Bibliographic reviews on theoretical foundations and information on cocoa marketing helping to understand and interpret the data obtained were made. Results showed that the small producers of National type cacao market their product through intermediaries, being these together with the exporters, the ones who benefit from the quality award instead of small producers. It is concluded that farmers who commercialize cocoa through associations receive a higher value than the intermediary pays, and in these cases, the associations provide advice and updated technical information